(untitled) (Journal of Civil Engineering Researchers, 2024)
This study explored the subsurface dynamics related to pile driving for the foundation of the E2 Bridge in Manta, Ecuador, using advanced geotechnical modeling. The objective was to evaluate the impact of various driving techniques on the mechanical properties of the soil, focusing on the stress distribution and the resulting deformations. The methodology included simulation analysis to compare different driving techniques and adjust them according to the specific soil characteristics at the construction site. The results revealed that by adapting the driving techniques to the local soil conditions, a 25% improvement in subsoil stability was achieved. The conclusions highlight the importance of customizing civil engineering practices according to the geotechnical specificities of each project. The adaptation of driving techniques is proposed as a practical and feasible measure to optimize construction processes, ensuring a more efficient and safer building. Furthermore, the study offers fundamental perspectives for the standardization of driving techniques in different geological contexts, contributing significantly to the improvement of foundation methodologies used in civil engineering.